The Role of ICT in Vocational Education and the Development of Information and Communication Technologies. Using the Opportunities of ICT in Education - Niyazmbetovich, Ahmadjon Nurimbetov; Madraimovna, Mambetova Sayyora; Sharofat, Jumaniyazova (European Journal of Life Safety and Stability (2660-9630), 2022)
As you know, information and communication technologies, microelectronics, computer technology (hardware and software), telecommunications and anti-electronics microprocessors, semiconductors and fiber optic cables in connection with discoveries in the fields.